Human capital formation and the American dust bowl - Arthi, V (2015)
I use variation in childhood exposure to the Dust Bowl, an environmental shock to health and income, as a natural experiment to explain variation in adult human capital. I also examine a variety of mechanisms by which the Dust Bowl influenced later-life wellbeing, and investigate the scope for recovery from this early-life shock. I find that exposure to the Dust Bowl in childhood has statistically significant and economically meaningful adverse impacts on later-life outcomes, for instance, increasing disability and reducing fertility and college completion. These results hold even after accounting for the possibly confounding effects of the Great Depression, migration, and selective fertility or mortality. The effects I find are more severe for those born in agricultural states, suggesting that the Dust Bowl was most damaging via the destruction of agricultural livelihoods. This collapse of farm incomes, however, had the positive effect of increasing high school completion amongst the exposed, likely by reducing the demand for child farm labor where such labor was not essential to production, and thus decreasing the opportunity costs of secondary schooling; in this outcome, unlike in college completion, family income and student ability were irrelevant. Many of the worst adverse effects are found amongst those exposed prenatally and in early childhood, suggesting that congenital complications in capability development, together with low parental incomes in utero and thereafter, may be to blame for such later-life disadvantage. Together, these findings imply that the Dust Bowl acted largely "indirectly," as an economic shock that in turn affected in utero and early-life conditions, rather than "directly," through personal exposure (e.g. dust inhalation) in childhood. Lastly, results - particularly those on New Deal expenditure - imply both that remediation from early-life disaster is possible under the right circumstances, and that post-shock investment may have compensated for rather than reinforced damage to child endowments. The findings in this study are consistent with a multi-stage model of human capability formation, in which investments in one period respond to endowments in a previous one, and may either reinforce or compensate for these endowments.